Bacterial vaginosis, alterations in vaginal flora and HIV genital shedding among HIV-1-infected women in Mozambique - Robert D Kirkcaldy; Jennifer Mika; Lori M Newman; Judite Langa; Linhui Tian; Ilesh Jani; Ron Ballard; Lisa Nelson; Elena Folgosa (AOSIS, 2011)
Objectives. We investigated whether abnormal vaginal flora, including bacterial vaginosis (BV), are associated with detection of cervical HIV-1 RNA among HIV-infected women in Mozambique. Methods. We obtained clinical data and vaginal specimens from HIV-infected women registering for their first visit at one of two HIV care clinics in Mozambique. We compared women with detectable cervical HIV viral load (≥40 copies/ml) with women with undetectable cervical HIV. Results. We enrolled 106 women. Women with abnormal vaginal flora (intermediate Nugent scores, 4 - 6) were more likely to have detectable cervical HIV RNA then women with normal vaginal flora (adjusted odds ratio 7.2 (95% confidence interval 1.8 - 29.1), adjusted for CD4 count). Women with BV had a non-significantly higher likelihood of detectable cervical HIV than women with normal flora. Conclusions. Abnormal vaginal flora were significantly associated with cervical HIV expression. Further research is needed to confirm this relationship.